Comparison Of Shear Bond Strength, Adhesive Remnant Index And Enamel Damage Using Different Light Source In Debonding Of Orthodontic Brackets - AlYamani, Helmi Abobakr Qaid (2011)
Light-curing orthodontic adhesives require light with sufficient intensity and defined wavelength to initiate polymerization. Insufficient light intensity and wavelength causes incomplete polymerization, which decreases shear bond strength (SBS) and render brackets unable to resist intra-oral forces of occlusion or orthodontic forces. During debonding of orthodontic brackets, adhesive remnants remain on the enamel surface and enamel damage (ED) may occur.